Comparison of two acidophilic sulfidogenic consortia for the treatment of acidic mine water - Frederico, Tayná Diniz; Nancucheo, Ivan; Santos, Werica Colaço Barros; Oliveira, Renato Renison Moreira; Buzzi, Daniella Cardoso; Pires, Eder Soares; Silva, Patricia Magalhães Pereira; Lucheta, Adriano Reis; Alves, Joner Oliveira; Oliveira, Guilherme Corrêa de; Bitencourt, José Augusto Pires (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Sulfate-reducing bioreactors are a biotechnological alternative for the treatment of acid mine drainage (AMD). In this study, two separate bioreactors with pH and temperature-controlled (Bio I and II) were operated with two different acidophilic microbial consortia to determine their efficiencies in sulfate removal from a synthetic acidic mine water. The bioreactors were operated for 302 days in continuous flow mode under the same parameters: fed with a sulfate solution of ~30 mM with a pH of 2.5, the temperature at 30 °C, stirred gently at 40 rpm and using a continuous stream of nitrogen to help remove the H2S produced in the bioreactor. The glycerol consumption, acetate production, and sulfate removal were monitored throughout the course of the experiment. The community composition and potential metabolic functional groups were analyzed via 16S rRNA partial gene sequencing. Bio I consortium reduced the sulfate, achieving a range of sulfate concentration from 4.7-19 mM in the effluent liquor. The removal of sulfate in Bio II was between 5.6-18 mM. Both bioreactors' communities showed the presence of the genus Desulfosporosinus as the main sulfate-reducing bacteria (SRB). Despite differences in microbial composition, both bioreactors have similar potential metabolism, with a higher percentage of microorganisms that can use sulfate in respiration. Overall, both bioreactors showed similar performance in treating acidic mine water containing mostly sulfate using two different acidophilic sulfidogenic consortia obtained from different global locations.